Advanced Hand Gesture Controlled Television Using Data - KUMAR, M. ASHOK; KUMAR, MR.D. (IJRDO -Journal of Computer Science Engineering, 2015)
Human interaction with wearable computers is a challenging research issue, especially when combined with augmented reality applications. Natural interaction with various devices should be simple and at the same time intuitive for any user. This project represents the design and implementation of a novel interactive hardware which recognizes certain hand gestures and responds in a way of controlling a remote television. The hardware is made as a data glove with an accelerometer and stretch sensor attached to it. Control parameters are calculated by an accelerometer and stretch sensor mounted on the glove, which detects positions of a user’s palm in a 3D space. Slow palm rotation is translated into commands for the volume control, ON/OFF, and channel switching. RF transmitter connected to the accelerometer sends the current palm and hand coordinates to the remote unit. The TV control is managed by an RF receiver and microcontroller which translates the received data to TV commands.